A Network-Based Peer Evaluation Strategy - Alket, Mohamed A (International journal of modern education and computer science, 2017)
The purpose of this study was to design a network-based peer evaluation strategy -which included two types of peer evaluation (known and unknown) to investigate the effect of these two types on developing problem-solving and critical thinking skills for students in Java object oriented programming language course (OOP). The participants of this study were twenty-four (n=24) students at College of Science and Arts, Qassim university. The results revealed that the two types of peer evaluation (in both known and unknown) had a positive effect on developing problem-solving and critical thinking skills for students. After, the comparison between the post-application of the two experimental groups in the problem solving and critical thinking skills, although there is a slightly higher between mean ranks in the sake of the unknown group, the results showed that there were no significant differences between the two groups. Finally, the researcher recommended to using a network-based peer evaluation strategy with other specializations and a large sample.